THE ROLE OF PLS FINANCING ON ECONOMIC GROWTH: INDONESIAN CASE - Masrizal, Masrizal; Trianto, Budi (Journal of Islamic Monetary Economics and Finance, 2022)
This paper investigates the role of PLS financing and non-PLS financing of Islamic banks in supporting the real sector for the case of Indonesia using monthly data from January 2009 to December 2018. Applying the ARDL approach to model their long-run and short-run relations, we find positive contribution of the PLS financing scheme to Indonesia's economic growth. Comparing the PLS and non-PLS financing, we note that the PLS financing has a larger impact on growth, both in the long run and short run. Accordingly, for Islamic finance to have larger growth impact, concrete steps and initiatives must be put in place to increase Islamic financing based on PLS arrangements.